THE IMPROVEMENT OF STUDENT'S CREATIVE THINKING ON THE THEME OF HEAT AND ITS TRANFER THROUGH THE PEER TEACHING METHOD AT ELEMENTARY SCHOOL OF PABERASAN I SUMENEP - Ali Armadi; M. Ridwan (Widyagogik, 2021)
This research has several objectives. First, applying peer-to-peer teaching methods to improve students' creative thinking on the theme of heat and its transfer, sub-themes of temperature and heat in class V at Elementary School of Paberasan I. Second, improving students' creative thinking through peer-teaching methods, the theme of heat and its transfer, sub-themes of temperature and heat in class V at Elementary School of Paberasan I. In the first cycle, the Indonesian language subjects obtained 58%, 50% for IPA, and 66% for SBdP, increased in the second cycle to 83% for Indonesian, 75% for IPA, and 92% for SBdP In the first cycle of creative thinking, students get 57% which is included in the creative enough category, and increases in the second cycle which gets 82% included in the creative category.